Investigating the impact of seaweed extract on the growth, yield and nutrient uptake of low-land transplanted rice (Oryza sativa L.) - BAGRECHA, SHREYAS; NITHINKUMAR, KADAGONDA; SAIKIA, NILUTPAL; MAHAPATRA, DEEPTIREKHA; MEENA, RAJESH KUMAR; MELAVANKI, MANJUNATH S.; VIJAY, FISKEY VRUSHABH (Journal of Soil and Water Conservation, 2025)
India is a resource-rich country with diverse climatic conditions and biodiversity. Seaweed syn. seagrass is present in the coastlines of India and their extract can be used as input in agriculture considering presence of biochemical compounds. An experiment of seaweed extract (SWE) based on Ascophyllum nodusum was conducted during the rainy season (Kharif) of 2021-2022 at the Agriculture Research Farm, Banaras Hindu University, Varanasi, India, to investigate the effectiveness of applying SWE on rice (Oryza sativa L.) growth, yield and nutrient uptake in lowland transplanted conditions. The study was conducted in a randomized complete block design with eight treatments and replicated three times. Treatments consists T1: untreated control; T2: 8 kg/ha; T3: 10 kg/ha; T4: 12.5 kg/ha; T5: 15 kg/ha; T6: 25 kg/ ha application of SWE twice at the tillering (TI) and panicle initiation (PI) stages; T7: 10 kg/ha of SWE only at TI; and T8: 10 kg/ha of SWE only at PI. The findings revealed that the SWE treatments had significantly higher growth parameters, yield attributes and yield than the untreated control. The plant height (119.20 cm), dry matter accumulation (51.3 g/hill), tiller per hill (8.97), leaf area index (7.68), SPAD value (36.8) and grain yield (5.5 t/ha) were recorded with the application of SWE at 25 kg/ha applied twice at the TI and PI stages (T6). Similarly, higher nutrient uptakes and nutrient harvest index were recorded in the same treatment T6. Therefore, the results demonstrated that lowland transplanted rice in Eastern Uttar Pradesh can benefit from the use of coastally derived seaweed extract (SWE at 25 kg/ha applied twice at the TI and PI stages) as a nutrient source to increase growth, productivity and quality.